The The Implementation of Initiation–Response–Feedback (IRF) in EFL Writing Class - Atmojo, Fajar Nugroho Dwi; Saleh, Mursid; Widhiyanto, Widhiyanto (Universitas Negeri Semarang, 2020)
Classroom interaction has been an interesting discussion in the research of discourse as well as language education itself. This research was aimed to analyze the implementation of initiation-response-feedback (IRF) model in EFL writing class. IRF is a pattern of classroom interaction found by Sinclair and Coulthard in 1975 that stands for teacher initiation, students’ response and feedback by teacher. This study was a case study with several steps conducted by its researcher in analyzing the data. The analysis of the data began with the process of organizing data from the result of recording, transcribing data into paper-based transcriptions, coding the data, calculating the occurences of the teaching exchange pattern and IRF pattern, reporting the findings, and interpreting the findings. The results of the study showed that both teacher and students implemented the IRF model in teaching and learning process, especially in writing class. In this study there are five teaching exchanges which occurred based on Sinclair and Coulthard (1975)’s model including teacher inform, teacher direct, teacher elicit, student inform, and check. Furthermore, the classroom interaction process in EFL writing class reflected the patterns of IRF sequence. As the conclusion, it is recommended that the teacher should maintain the effectiveness of classroom interaction and give much opportunity to the students to take role in classroom verbal interaction through reflecting the IRF pattern in teaching learning process particularly in EFL writing class.